2002
DOI: 10.1097/00004728-200205000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Carcinoma: Findings at MR Imaging With MR Cholangiopancreatography

Abstract: MRI and MRCP can provide information relevant to preoperative staging of gallbladder carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 20 publications
4
43
0
5
Order By: Relevance
“…In our series, MRI and PET-CT were not always performed to gain more information of tumor spread. The diagnosis of lymph node involvement by these imaging modalities was not superior to that of CT in this study as well as previous reports [6][7][8]20], although precise analyses of the diagnostic power of CT and other modalities were not performed.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In our series, MRI and PET-CT were not always performed to gain more information of tumor spread. The diagnosis of lymph node involvement by these imaging modalities was not superior to that of CT in this study as well as previous reports [6][7][8]20], although precise analyses of the diagnostic power of CT and other modalities were not performed.…”
Section: Discussionsupporting
confidence: 72%
“…PET and high-resolution MRI have been considered additional modalities to improve diagnostic accuracy [6][7][8]20], although the PPV was similar to that of CT. Schwartz et al [7] reported that the accuracy was similar for CT and MRI. Furukawa et al [8] indicated the limitations of resolution of PET-CT imaging for lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2) (11). Schwartz et al (12) showed that GBCA manifested at MRI as focal gallbladder wall thickening with an eccentric mass in 76% of cases. GBCA is typically T1 hypointense and T2 hyperintense compared with the surrounding liver parenchyma (Figs.…”
Section: Mri Featuresmentioning
confidence: 99%
“…Hence, high resolution T2 and arterial phased contrast enhanced images are most useful in differentiating GBCA from inflammatory wall thickening. The late phases of enhancement are less useful, as delayed wall enhancement is present in both cholecystitis and GBCA (12).…”
Section: Chronic Cholecystitismentioning
confidence: 99%